PERAN GURU BOARDING SCHOOL DALAM MENINGKATKAN AKHLAK SISWA KELAS IX SEKOLAH MENENGAH PERTAMA PANDANARAN PLUPUH SRAGEN - Permadani, Pandu Nova; Fathurrohman, Mukhlis (Jurnal Manajemen Pendidikan, 2025)
This study is grounded in the growing challenges of moral education for adolescents amid globalization, digital culture, and declining politeness, worship discipline, and responsibility. SMP Pandanaran Plupuh Sragen, as a boarding school, strongly aspires to nurture young generations with noble character, Pancasila values, independence, health, and academic excellence. The research aims to describe the roles of teachers, homeroom teachers, and dormitory guardians in modelling and habituation; teachers’ roles in moral assessment, rule enforcement, and gadget supervision; and teachers’ roles in communication and synchronization with parents. A qualitative approach with a descriptive design was employed. The study was conducted at SMP Pandanaran Plupuh Sragen. The subjects consisted of teachers, ninth grade homeroom teachers, dormitory guardians, ninth grade students, and several parents selected purposively. Data were collected through participant observation, in-depth interviews, and document analysis, then analyzed interactively using data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The findings reveal that the role modelling of teachers, homeroom teachers, and dormitory guardians, reinforced by structured habituation programs in worship, discipline, and independence, significantly contributes to students’ moral improvement.